The IL‐33‐ST2‐MyD88 axis promotes regulatory T cell proliferation in the murine liver. Issue 8 (25th May 2018) - Xu, Lei; Li, Wei; Wang, Xiaofan; Zhang, Lina; Qi, Qianqian; Dong, Liyang; Wei, Chuan; Pu, Yanan; Li, Yalin; Zhu, Jifeng; Zhou, Sha; Liu, Feng; et al.
Abstract: Hepatic Foxp3 + Treg cells are crucial for maintaining local immune homeostasis in the liver. However, the environmental cues required for hepatic Treg cell homeostasis are unclear. In this study, we showed that the IL‐33 receptor ST2 was preferentially expressed on Treg cells in the mouse liver, but it was more lowly expressed in the spleen, mesenteric lymph nodes, and blood. More importantly, we found that IL‐33 promoted the proliferation of hepatic Treg cells through myeloid differentiation factor MyD88 signaling concomitant with increased cyclin‐dependent kinase 4 and cyclin D1 expression. These results suggest that IL‐33 is a potential tissue‐specific factor controlling Treg cell homeostasis via increased Treg proliferation in the liver. Abstract : IL‐33 receptor ST2 is preferentially expressed on hepatic Treg cells. IL‐33/ST2 signaling promotes hepatic Treg cell expansion through MyD88, correlated with increased CDK4 and cyclin D1 expression.